Konsep Dasar Kepemimpinan Pendidikan dalam Mengenali Potensi Peserta Didik Generasi Alpha - Asagina Sabila; Adinda Azzahra Salsabila; Ahmad Sabri; Rully Hidayatullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Generation Alpha is a unique generation, born in the era of digital technology. Since an early age, they have been in contact with information technology. Based on previous research, this generation spends a lot of time in front of the screen and is fluent in using technological tools. As a generation of future leaders, teachers and parents must have an approach based on the characteristics of the Alpha generation in parenting and teaching patterns to develop leadership character. The study aims to examine the characteristics of the Alpha generation, how character education for the Alpha generation and effective parenting patterns in preparing the digital leadership of the Alpha generation. Literature studies show that the Alpha generation has great potential as a digital leader through the digital environment, character education in schools and parental care must be adjusted to the characteristics of the Alpha generation, by providing role models, mentoring, and good relationships. This study used a mixed method involving a quantitative survey of teachers and students, as well as qualitative interviews with school principals. The results of the study show that effective leadership in this context involves the implementation of holistic policies, which not only emphasize mastery of technology, but also strengthen character values ​​such as responsibility, discipline, and empathy. Thus, the role of principals and teachers is crucial in creating a learning environment that is balanced between the intellectual development and character of students. This research provides strategic recommendations for educational leaders in designing policies that are able to integrate technology without neglecting student character development.